Assessment of molecular variation in the known Pericarp colour related genes in purple rice (Oryza sativa L.) - Huidrom, Thoithoi; Pattanayak, A. (Umiam : CPGS, CAU, 2012)
Coloured rice, mainly red and purple rice is grown in limited areas or as specialty rice. Chak - hao Poireiton is one such purple rice which is grown as a specialty rice mainly in the Indian state of Manipur. In the present investigation, a total of 26 primer pairs were tested on 8 genotypes with varying pericarp and endosperm colour to assess the molecular variation in the known pericarp colour related genes in purple rice (Oryza sativa L). In the present study,the Ra gene marker produced a 230 bp band (instead of 853bp) and did not show any restriction digestion in any of the purple / white pericarp test genotypes. Although it is premature to draw a definite conclusion, it is possible that the purple colour in the rice genotype Chak - hao Poireiton (and its progeny) is controlled by some other gene or a different allele of Ra gene. The primer AF-12 amplified a fragment where, in genotype 12 (Daya- white pericarp), a new deletion was seen immediately after the 'G string' of Rc-g. In two of the test genotypes, which had white pericarp, a deletion in the 'G string' was observed without the 14 bp deletion. Several other transition and transversions were seen in different genotypes but the characteristic 14bp deletion was absent in all test genotypes. The primer pair of RC-11 amplified a fragment within the exon 3. SNP's were detected in the test genotype. The effect of these changes on amino acid sequence revealed the deletion of a stop codon in the genotype 12. RC5 - 012 amplified fragment which was in the exon 2 of the gene cycloartenol-C-24-methyltransferase 1. Sequence comparision showed single nucleotide changes at several positions. The effect of these changes on the amino acid sequence was not very large. However the most conspicuous change was the removal of the stop codon in genotype 13 (Chak - hao Poireiton). The maximum likelihood tree constructed from the haplotype data identified the genotype 13 as a very distant genotype from the reference genotypes as well as the male parent Daya. Our results suggest that deletion at the 'G string' without the 14bp deletion can produce a white pericarp phenotype.
Keywords: Molecular variation -- Purple Rice; Pericarp colour -- Genes